2018
DOI: 10.1002/mnfr.201800947
|View full text |Cite
|
Sign up to set email alerts
|

Excess Dietary Zinc Intake in Neonatal Mice Causes Oxidative Stress and Alters Intestinal Host–Microbe Interactions

Abstract: Scope Greater than 68% of young infants are exposed to dietary zinc (Zn) levels that are higher than the Tolerable Upper Intake Limit. However, the consequences of excess dietary Zn during early life on intestinal function and host–microbe interactions are unknown. Methods and Results Neonatal mice are gavaged with 100 Zn µg d–1 from postnatal day (PN) 2 through PN10 and indices of intestinal function and host–microbe interactions are compared to unsupplemented mice. Excess dietary Zn causes oxidative stress, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…It was recently reported that excess dietary Zn causes oxidative stress, enhances gut permeability, and modifies the microbiota in mouse pups 108 . However, metal absorption, gene regulation, gut permeability, lack of strong innate and adaptive immunity, and the concept of dysbiosis in neonates may differ considerably from the integrated physiologic processes in adults.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that excess dietary Zn causes oxidative stress, enhances gut permeability, and modifies the microbiota in mouse pups 108 . However, metal absorption, gene regulation, gut permeability, lack of strong innate and adaptive immunity, and the concept of dysbiosis in neonates may differ considerably from the integrated physiologic processes in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary zinc–curcumin supplementation improved the gut dysbiosis associated with zinc dysregulation and the cardiotoxicity induced by doxorubicin in rats (Wu, et al , ), providing a basis for future clinical studies to support the development of novel approaches for cardiotoxicity prevention. However, zinc supplementation affected the gut microbial composition in a dosage‐dependent manner (Watson, et al , ), and excess dietary zinc increased intestinal permeability and enriched pathogenic gut microbial species (Podany, et al , ), suggesting that zinc levels have critical effects on the susceptibility of individuals to pathogenic effects and disease severity.…”
Section: Gut Microbiota Interventions For Cvdmentioning
confidence: 99%
“…Zinc is necessary for the function of Paneth cells, which prevent pathogenic microbial invasion in the intestine, a risk for subsequent hepatic inflammation via α-defensin production [105]. However, the presence of excess dietary zinc increases oxidative stress with an increased intestinal permeability that should be avoided [106]. An appropriate and effective supplementation strategy is therefore necessary, even for trace elements.…”
Section: How To Manage Oxidative Stress In Pre-cancer Stagementioning
confidence: 99%